Virtualization based network measurement platform - Zheng CAO; Jian-bin HE (Tongxin xuebao)
With the expansion of network measurement research,the network measurement infrastructures must support the extensible to different network environment and services while improving performance at the same time.A network measurement platform based on virtualization technology was presented,by discussing the key issues of the platform,design of the virtual platform and its operation mechanism.The instance of a multicast measurement shows that compared with the existing measurement platforms,the virtualization platform has concurrency,scalability,customization and reconfigurability characteristics.